Anthropology - Ember, Carol R.; Ember, Melvin (Englewood Cliffs, New Jersey : Prentice-Hall, 1985)
n revising our book for this edition, we have been motivated by two considerations. One is the ordinary one of wanting to incorporate recent achievements of anthropological research. The second is to make more explicit the difference between theory and data, because to do so communicates the principle that all explanations are somewhat uncertain, and that some are more uncertain than others. Motivated by this second consideration, we have added an entirely new chapter on explanation and evidence. We believe it is important for students to learn what it means to explain, and what kinds of evidence are necessary to evaluate an ex-planation. We do not think that our educational system has typically done a good job of communicating the tentativeness of knowledge. All too of-ten, especially in the lower grades, things are taught as if they were absolutely true. Little uncertainty is conveyed, and students learn next to nothing about the process of research. In this edition we try to convey more explicitly the idea that all scientific understanding is tentative and subject to revision. Our philosophy about what a textbook should be remains the same. Above all, we want our book to be as scholarly as possible. At the same time, we want it to be as readable and exciting as possi-ble. One of the things that makes teaching introductory anthropology so much fun for us is the irrepressible curiosity of beginning students. Anthropology is largely new to them, and they want to know about the world beyond their usual pur-view$1 (Bto learn about it and to try to understand it. They ask innumerable questions, some that anthropologists can answer, others that cannot be answered as yet. In this edition of our text, as in the previous ones, we have tried to gear our presentation to the kinds of questions students as well as anthropologists have asked about human evolution and variation. Our aim is to capitalize on the curiosity of students about how and why human populations have come to be what they are.s
Introduction to anthropology -- What is anthropology -- Human evolution -- Biological and Cultural Evolution -- The surviving primates -- Primative evolution from early primates to hominids -- Early hominids and their cultures -- The emergence of homo sapiens and middle and upper Paleolithic cultures -- Human variation -- Origins of food production and settled life -- Origins of cities and states Cultural variation -- The concept of culture -- Schools of thought in cultural anthropology -- Explanation and evidence -- Language and culture -- Food-getting -- Economic systems -- Social stratification -- Sex and culture -- Marriage and the family -- marital residence and kinship -- Associations and interest groups -- Political organization -- social order and disorder -- Psychology and culture -- Religion and magic -- The arts Culture and anthropology in the modern world -- Culture change -- Applied anthropology.
Includes bibliographical references and index.
Keywords: ANTHROPOLOGY